2017
DOI: 10.1007/s10068-017-0293-x
|View full text |Cite
|
Sign up to set email alerts
|

The phytochemical rich potential of acorn (Quercus aegilops) products and by products

Abstract: The phytochemical content of acorn () products (nuts and flour) and by products (shells and leaching waters) regarding their content in total phenols, fatty acids, sodium, potassium and calcium was investigated. Antioxidant activity was also examined. Acorn materials presented high total phenol content (up to 47.6 ± 0.6 mg gallic acid equivalents (GAE)/g dry material), with a substantial amount remaining after leaching (11.6 ± 0.7 mg GAE/g flour), and high DPPH radical scavenging and ferric reducing activity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…The antioxidant activity of the materials was examined by the application of the FRAP assay in the aqueous olive leaf extracts and the DPPH radical scavenging activity in the alcoholic extracts. The methods employed are commonly applied for the analysis of many matrices [43] such as nuts [44], vegetable oils [45], fruits, and relevant products [26,46,47,48]. All the examined polar extracts (aqueous, methanol, and ethanol) presented similar trends (Figure 6, Table A1).…”
Section: Resultsmentioning
confidence: 89%
“…The antioxidant activity of the materials was examined by the application of the FRAP assay in the aqueous olive leaf extracts and the DPPH radical scavenging activity in the alcoholic extracts. The methods employed are commonly applied for the analysis of many matrices [43] such as nuts [44], vegetable oils [45], fruits, and relevant products [26,46,47,48]. All the examined polar extracts (aqueous, methanol, and ethanol) presented similar trends (Figure 6, Table A1).…”
Section: Resultsmentioning
confidence: 89%
“…None of these procedures significantly influenced the taste assessment of products made of acorn flour. Papoti, Kizaki, Skaltsi, Karayannakidis, and Papageorgiou (2018) evaluated the impact of leaching by soaking acorns in lye on total phenolic content, including tannins. They found that the flour from leached acorns contained nearly three times less phenolic compounds than the untreated raw material.…”
Section: Acorn Flour Productionmentioning
confidence: 99%
“…Most acorn types, indeed, show a high content of tannins, which are astringent and behave as anti-nutrients (Papoti et al., 2018). In the past, local populations identified and selected the trees bearing sweeter acorns, directly used for edible purposes, whereas the excessively astringent or even bitter acorns, which resulted unpalatable, were subjected to appropriate heat treatments and leaching (Papoti et al., 2018; Pignone and Laghetti, 2010; Rakić et al., 2007) or detoxification with clay (Johns and Duquette, 1991). However, nowadays the knowledge related to the use of acorns as food remains only in the memories of the elderly and is being lost.…”
Section: Introductionmentioning
confidence: 99%
“…The lipid fraction is characterized by high levels of unsaturated fatty acids (Al-Rousan et al., 2013; Özcan, 2007). In addition, recent studies highlighted that acorns have a rich phytochemical potential, mostly represented by phenolic compounds (Papoti et al., 2018; Vinha et al., 2016), and display interesting biological activities (Vinha et al., 2016) such as anti-inflammatory and anti-asthma effect (Moon et al., 2013), and a role in the prevention of obesity, dementia and liver diseases (Kang et al., 2004; Lee et al., 2005).…”
Section: Introductionmentioning
confidence: 99%